CORRELATION OF GLYCOSYLATED HEMOGLOBIN LEVELS WITH FASTING AND POSTPRANDIAL GLUCOSE IN SOUTH INDIAN TYPE 2 DIABETIC PATIENTS - Haghighatpanah, Mohammad; Thunga, Girish; Khare, Sarvajeet; Mallayasamy, Surulivelrajan (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To assess the correlation of glycosylated hemoglobin levels with fasting and postprandial glucose in South Indian type 2 diabetic patients. Methods: This retrospective observational study was carried out as per the protocol approved by the institutional ethics committee (IEC) and case records of patients (â‰¥ 40 y old) diagnosed with type 2 diabetes mellitus (T2DM) and complications, that fasting blood sugar (FBS), postprandial blood sugar (PPBS) and HbA1c measured during previous follow-ups were included in the study. Statistical analyses were carried out using SPSS Ver.20 and p â‰¤ 0.05 were considered statistically significant. Results: Based on the study criteria, 633 case profiles were selected and enrolled in the study. Most of the patients were males 488 (77.1%) and the mean age of patients was 59.7 y (SD=9.6). The mean fasting glucose and postprandial glucose were 9.42 mmol/l (SD=4.2), 13.39 mmol/l (SD=5.2) respectively. Patients were suffering from different type of diabetes complications, and most of them had poor glycemic control as the mean HbA1c was found to be 8.7 % (SD=2.2). The FBS and PPBS were plotted against HbA1c values showed moderate correlation and the sensitivity, specificity, positive predictive value and negative predictive value of postprandial glucose level was better than the fasting blood glucose level. Conclusion: This present study showed that there is the significant correlation between PPBS and HbA1c values. Since PPBS is performed routinely, its interpretation in terms of long term glycemic control will help clinicians to tailor their therapeutic strategies.